DEALING WITH STUDENTS’ RETICENCE IN SPEAKING ACTIVITY IN EFL CLASSROOM - Jenal Aripin; Amalul Umam (ENGLISH, 2019)
Speaking is an activity in an English classroom in which students must integrate not only higher order thinking skills but also confidence. As a result, it can be problematic for students because they feel shy or reticent. This study aimed at finding out the cause of students’ reluctance in speaking activities. The study was framed by using classroom action research in which 2 cycles were employed. Each cycle consisted of four stages: planning, action, evaluation, and reflection. There were 40 students in the 7th grade of junior high school in Bogor as the participants of the study. The data was collected through documentation, observation, and semi-structured interviews. The results showed that the causes of students' reluctance in speaking class were shy, lazy, afraid and ignorance. Giving more students’ talk time as a teaching strategy in English speaking activity can be done to reduce students’ reticence.